A Cultural History of the Disneyland Theme Parks : Middle Class Kingdoms - Mittermeier, Sabrina (Intellect, 2020)
The first comparative historical study of the six Disneyland theme parks around the world in five distinct cultures: the USA, Tokyo, Paris, Hong Kong and Shanghai. Situates the parks in their respective historic contexts at the time of their opening, and considers the part that class plays in the success or failure of these ventures.
Knowledge Unlatched
English
Keywords: Adventure; Fiction; Action & Adventure